Strategic Leadership and Service Delivery in Organizations: A Critical Review of Literature - Ragul, Vitalis (My University, 2021)
Strategic leaders need to be certain about what they want to achieve for the organization. Efficient and effective leaders develop strategies and structures that are clear and work with employees that adhere to good ethical practices that enable the organizations to achieve set goals. Strategic leadership is important to all organizations, whether in public and private sector, albeit in different contexts. This paper sought to critically review literature on the link between strategic leadership and service delivery in organizations. Several theories were reviewed, namely upper echelons perspective, strategic leadership theory, principal agency theory and new public management theory. A conceptual framework was developed to provide the basis of the identified theories with a view to explaining and predicting the variables through definition of the contents and attributes of those theories. Strategic leadership was conceptualized as the independent variable while service delivery in organizations was hypothesized as the dependent variable. Conceptual and empirical studies were undertaken to examine the existing literature in strategic leadership as well as service delivery. Arising from the review, several knowledge gaps were identified. The study established that strategic leadership is applicable to all organizations with an increasing number of organizations continually embracing it upon realizing that it is a key success factor in organizational performance and therefore in the delivery of service for the benefit of the public.
Keywords: Strategic leadership; Service delivery; Public sector; Citizens